Análise de protótipo de vigas baldrame submetido a ação agressiva da água - Melo, Eduardo Silva (2019)
This paper’s purpose was to prove the benefits of sealing structures on constructions through a study about water absorption and the capillary absorbency on foundations. For this experiment was built prototypes of the foundation and the first brick row, where some of them remained without sealing, some of them was sealed only on the foundation and some of them was sealed on the foundation and on the mortar of the first brick row. The difference of weight of the prototypes with and without sealing wasn’t subtle. This information proved the initial theory of the foundation’s property of absorption by capillarity and confirmed the relevance of a good sealing on ´building construction.